Are Women of East Kazakhstan Satisfied with the Quality of Ma¬ternity Care? Implementing the WHO Tool to Assess the Quality of Hospital Services - Marzhan DAULETYAROVA; Yuliya SEMENOVA; Galiya KAYLUBAEVA; Gulshat MANABAEVA; Zayituna KHISMETOVA; Zhansulu AKILZHANOVA; Akylbek TUSSUPKALIEV; Zhazira ORAZGALIYEVA (Tehran University of Medical Sciences, 2016)
Background: To evaluate the satisfaction of mothers with the quality of care provided by maternity institutions in East Kazakhstan on the basis of the "Quality of hospital Care for mothers and newborn babies, assessment tool" (WHO, 2009). Methods: This cross-sectional study took place in 2013 and covered five maternity hospitals in East Kazakhstan (one referral, two urban and two rural). To obtain information, interviews with 872 patients were conducted. The standard tool covered 12 areas ranging from pregnancy to childcare. A score was assigned to each area of care (from 0 to 3). The assessment provided the semi-quantitative data on the quality of hospital care for women and newborns from the perception of mothers. Results: The average satisfaction score was 2.48 with a range from 2.2 to 2.7. The mean age of women was 27.4 yr. Forty-two percent were primiparas. Mean birth weight was 3455.4 g. All infants had 'skin to skin' contact with their mothers immediately after birth. Mean number of antenatal visits to family clinics was 8.6. Only 42.1% of the respondents used contraceptives while the rest were not aware of contraception, never applied it and could not distinguish between different methods and devices. Conclusions: The quality of care was substandard in all institutions. To improve the quality of care, WHO technologies in perinatal care could be applied.   Keywords: Maternal health care, Quality of care, WHO assessment tool, Kazakhstan